Contributo para o conhecimento do coberto vegetal no decurso do 3.º milénio a.C. na região de Oeiras: resultados dos estudos antracológicos de Leceia - Monteiro, Patrícia Diogo (2019)
In this article we present the results of the analysis of the anthracological remains collected during excavations in the prehistoric settlement of Leceia (Oeiras, Portugal). It was possible to identify, through the microscopic observation the fracture surfaces of 148 specimens several species that were part of the region‘s arboreal cover during the 3rd millennium BC, such as Arbutus unedo, Pinus pinaster, Olea europea, Pistacia lentiscus, Quercus ilex / Q. coccifera, Quercus subg. Quercus, in addition to other taxa that were not identified at the specific level.